The Use of Electrochemotherapy as Neoadjuvant Treatment for Head and Neck Cancer. (2nd September 2014) - Domanico, Rossana; Trapasso, Serena; Franco, Teresa; Allegra, Eugenia
Abstract : Objectives: Electrochemotherapy (ECT) is a cancer treatment based on the transport of chemotherapic drugs such as cisplatin and bleomycin into cell cytosol through depolarization of cell membrane. A locally applied electric field modifies the membrane permeability allowing intracellular accumulation of the chemotherapeutic agent. Methods: Prospective study: 12 patients with head and neck cancer treated with ECT with bleomycin at the ENT Department of Catanzaro teaching hospital from January to December 2013 were recruited. The primary endpoint of the study was ECT efficacy in the neoadjuvant treatment of head and neck cancer. For each patient clinical‐anamnestic data were collected in a database and the local tumor control, survival, and effects on quality of life (Health Survey Questionnaire, SF‐36 [v1], and Quality of Life Questionnaire, EORTC QLQ‐C30, and EORTC QLQH&N35) and pain control (Analgesia Post‐Surgery, APS scale) were evaluated. The treatments were performed by Cliniporator IGEA according to the European Standard Operating Procedures of Electrochemotherapy (ESOPE, 2006). Response to ECT treatment was evaluated after 30 days. All patients received postoperative chemoradiotherapy. Results: Local control and impact on quality of life were evaluated. Six of 12 lesions exhibited a partial response, 4 of 12 exhibited a complete response, and in 2 cases disease progression was observed. Conclusions: ECT represents a safe and effective therapeutic approach that is associated with clear benefits in terms of quality of life (minimal discomfort, mild post‐treatment pain, and short duration of hospital stay).